Dashboard Monitoring Kinerja Aparatur Sipil Negara Pada Dinas Pengelolaan Pajak Provinsi Kepulauan Riau - Okta Veza veza; Nofri Yudi Arifin; David Saro; Rio Adam (STEKOM PRESS, 2020)
Over time, the Riau Kepualaun Provincial Tax Management Office which lives in Batam City underwent a name change to become a Regional Tax and Retribution Management Agency for the Riau Islands Province (BP2RD). This study aims to design a dashboard that can assist Eschelon officials in monitoring the performance of the State Civil Apparatus (ASN) at the Regional Tax and Retribution Management Agency of the Riau Islands Province. Because there is no system that displays information related to the work done and completed by an ASN, a dashboard design is needed. Data on the dashboard system is obtained from ASN performance data consisting of activity grouping data, activity weights, monthly targets in one year, and distribution of incentives and employee income benefits based on the achievement of target weights. The modeling system used is the Unified Modeling Language (UML), with the use case, activity, sequence and class diagram stages. While the development of this research system uses the Macro Process method in Object Oriented Analysis Design (OOAD) with the stages of Requirements, Analysis and Design, Implementation and Testing. The dashboard is designed based on a website, using the PHP programming language and using MySQL as the database. Qualitative research techniques, by collecting data and information descriptively. The results of this study display a dashboard in the form of text consisting of the number of employees, targets, target achievement, target percentage, target employee income allowances, and employee income allowances obtained, as well as a dashboard in the form of a pie chart and bar chart for target and achievement percentages respectively. target, it is hoped that this dashboard can assist Eschelon Officials in assessing and monitoring the performance of the State civil apparatus.